α-helix formation rate of oligopeptides at subzero temperatures - Qin, Zhi-jie (Biophysics (Nagoya-shi), 2014)
In 1999, Clarke et al. ((1999) Proc. Natl. Acad. Sci. USA 96, 7232–7237) reported that the nucleation rate of α-helix of oligopeptide AK16 is as slow as 60 ms. In the present study, we measured the nucleation rate of oligopeptide, C17 (DLTDDIMCVKKILDKVG, corresponding to α-helical region of 84th to 100th amino acids of bovine α-lactalbumin) using the same method as Clarke et al. We found only initial bursts of the increase of α-helices at temperatures higher than −50°C in the presence of 70% methanol. The result with AK16 was the same as Clarke et al. reported. We also found that the folding rate of polyglutamic acid is too fast to be detected by the stopped-flow apparatus at 4°C. These results demonstrate that the α-helix formation rates in C17, AK16 and polyglutamic acid are shorter than the dead time of the stopped-flow apparatus (6 ms).